Postharvest losses and the impact of reusable plastic container technology on profitability: Evidence from tomato traders in Nigeria - Aghadi, Crystal N.; Balana, Bedru; Ogunniyi, Adebayo (International Food Policy Research Institute, 2020)
Postharvest loss is a major challenge in food production and supply chains in developing countries. Using primary data from fresh tomato traders in Lagos, Nigeria, and endogenous switching econometric modelling, this study investigates the effects of reusable plastic containers (RPC) technology on traders’ net profits and the factors determining the adoption of the technology. Results indicate that the trader’s position along the supply chain, income level, seasonality, sales frequency, and technology affordability positively influence their adoption decision. We found that the use of RPC technology significantly increases traders’ net profits. The counterfactual impact analysis indicates that traders who adopted RPC would have earned 7 percent lower net profits had they not used RPC. Conversely, non-adopters would have increased their net profit by 5 percent had they adopted the technology. However, heterogenous treatment effects were observed due to heterogeneities among the adopters.